Optimalisasi Digital Marketing Dan Product Branding Sebagai Strategi Pemasaran Produk Mikasi Drink Di Desa Pulosari, Kab. Jombang - Oktavia Shintianingrum; Zawawi Zawawi (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Over time, continuous technological developments should be used in the implementation of//product branding and digital marketing//by MSMEs players.//Digital technology-based marketing also provides opportunities for MSMEs, to develop further//and become part of Indonesia's economic recovery. That is why product branding and digital marketing assistance are needed. Therefore, the author created a community service program that offers, product branding and digital marketing assistance. Mikasi Drink MSMEs engaged in the culinary or beverage industry are one of our main targets in this work program. The FGD (Focus Group Discussion) method used in the method of implementing product branding and digital marketing-support. This work program succeeded in providing an understanding to MSMEs players of the importance of utilizing information technology for product branding and marketing. The author hopes that MSMEs players who get the assistance program will continue to implement it and innovate with the development of information technology.